Фазовий метод виявлення обривів в статорних обмотках асинхронних двигунів - Yenikieiev, Olexander; Kuts, Yurii; Tkachenko, Andrii; Sherbak, Leonid (General Energy Institute of the National Academy of Sciences of Ukraine, 2024)
The paper considers the specific features of the technical operation of asynchronous motors in hoisting machines and typical damages to stator windings. It is established that one promising approach to motor protection is the use of computer monitoring systems. These systems' algorithmic and application software includes measuring and controlling stator winding currents. A method for calculating the operating modes of asynchronous motors with a break in one of the parallel branches of the stator phase winding is developed. Based on the derived equations, a computer simulation scheme was compiled using the graph method in the MatLab software environment with the Simulink extension to calculate the symmetric and asymmetric operating modes of an asynchronous motor, considering the current distribution in the parallel branches of the phase windings, and the results of theoretical studies are experimentally confirmed. As a result, graphs are provided to show the relationship between the steady-state temperatures of the stator windings' frontal sections and the values of the phase currents. It is shown that current overload of the operating branch of the damaged phase winding can occur even at the nominal linear current. At the same time, in the operating parallel branch of the phase winding with a break, there is a significant thermal overload, which leads to rapid degradation of the winding insulation materials and the development of a malfunction to a more serious one. A characteristic feature of the operating mode of an asynchronous motor with a break in the parallel branch of the stator phase winding is that at a reduced load, the motor can operate for an extended period without overheating. It is demonstrated that the nature of the asymmetry of linear currents by phase can be used as a diagnostic indicator.